Metabolomics Evaluation of Serum Markers for Cachexia and Their Intra-Day Variation in Patients with Advanced Pancreatic Cancer - Yutaka Fujiwara; Takashi Kobayashi; Naoko Chayahara; Yoshinori Imamura; Masanori Toyoda; Naomi Kiyota; Toru Mukohara; Shin Nishiumi; Takeshi Azuma; Masaru Yoshida; Hironobu Minami (2014)
Purpose Cancer cachexia is a multifactorial syndrome characterized by progressive loss of weight and muscle atrophy. Using metabolomics, we investigated serum markers and their intra-day variation in advanced pancreatic cancer patients with cachexia. Methods Patients were enrolled in two groups: those with or without cachexia. Blood samples collected at 6:30 AM, 11:30 AM, 4:30 PM, and 9:30 PM were analyzed using metabolomics, and serum levels of IL-6, TNF-α, and leptin were measured and compared between the two groups. Intra-day variation was then evaluated. Results Twenty-one patients were enrolled in total. In the cachexia group (n = 9), median body weight loss rate over 6 months was greater, performance status was poorer, and anorexia was more severe than in the non-cachexia group (n = 12). Each metabolites level showed substantial intra-day variation, and some of them displayed significant differences between the two groups. Levels of paraxanthine remained markedly lower in the cohort with cachexia at all measurement points. Besides, median IL-6 and TNF-α levels appeared higher and leptin concentration appeared lower in the cachexia group, albeit without statistical significance. Conclusion Some metabolites and some serological marker levels were affected by cancer cachexia. Although paraxanthine levels were consistently lower in patients with cachexia, we identified that many metabolites indicated large intra- and inter-day variation and that it might be necessary to pay attention to intra-day variation in metabolomics research.